Hinokitiol Enhanced Vegetative Growth Parameters of Tomato cv. Falkato Compared with Salicylic Acid and Paclobutrazol under In Vitro Salinity Condition - Behrooz ESMAEILPOUR; Hassan MALEKI LAJAYER; Leila KESHVARZI; Younes POURBEYRAMI HIR (Notulae Scientia Biologicae, 2012)
The aim of this study was to assess the potential in vitro effect of hinokitiol on improvement of tomato seedling resistance to salinity stress. Effect of hinokitiol was compared with two anti-stress compounds, salicylic acid and paclobutrazol. Leaf numbers, shoot and root fresh weight and root fresh weight were recorded after about 8 weeks. Salt stress was accomplished by application of two levels of pure NaCl (50 and 100 mM) on MS basal medium. The treatments consisted of different concentrations of hinokitiol (0, 1, 5 and 10 ppm), paclobutrazol (0, 1, 2 and 4 ?M) and salicylic acid (0, 0.01, 0.1 and 1 mM). Results revealed that salinity blocked seed germination in media containing only 100 mM of pure NaCl without any treatment. In general all three compounds increased tomato seedling growth, indicating these compounds are able to alleviate the negative effect of salinity on tomato plants. However, Hinokitiol was the most efficient compound. Compared with SA, application of hinokitiol significantly increased leaf numbers, shoot length and shoot and root dry weight. Also, media containing different concentrations of hinokitiol produced higher root and shoot fresh weight than control and other treatments. Future physiological studies are needed to clarify the mechanism of induction of salt tolerance activity by hinokitiol.